Design and parameters optimization of root cutting tool based on garlic numerical simulation model. (17th May 2021) - Chen, Jianneng; Zhou, Binsong; Jia, Jiangming; Chen, Zhiwei; Yu, Chennan; Cai, Shuanglei
Abstract: To obtain the best tool parameters for garlic root cutting to reduce the root cutting force and improve efficiency, a linkage occlusion‐cutting mechanism was designed for a garlic root cutting force test. The physical and mechanical properties of garlic meat and garlic skin were measured and calculated by using a universal material testing machine. A plastic follow‐up model (MAT‐3) in the LS‐DYNA material library was used as a simulated garlic material model. A three‐dimensional model of the garlic and the tool was established and imported into ANSYS/LS‐DYNA to establish a garlic root cutting simulation model. The model was used for numerical calculation and analysis. The simulation parameters were optimized according to the actual cutting force change curve, and a reliable simulation model was obtained. The error between simulated result and actual measurement was 3.5%. Based on this reliable model, the effects of tool parameters on the root cutting force were explored. The optimal blade edge angle was 11°, the optimal blade back angle was 13°, and the cutting root force was reduced by 14.94%. The reliable model and optimal tool parameters provide a reference for the design and development of garlic root cutting equipment. Practical Applications: Garlic is popular worldwide because of its high nutritional value and unique flavor. A reliable numerical simulation model for garlic will encourage researchers to design garlic‐processing equipment. The optimal tool parameters also provide a reference for garlic root cutting equipment. Abstract :